Infrared, Thermal and X-rays Diffraction Analysis of Dysprosium Soaps - UPADHYAY, S.K.; SHUKLA, R.K.; SHARMA, GOVIND (Asian Journal of Chemistry, 2010)
The physico-chemical characteristics of dysprosium soaps (butyrate and valerate) in solid state were investigated by IR, thermal and X-ray diffraction measurement, the IR results reveal that the fatty acids exist in dimeric state through hydrogen bonding and soaps possess partial ionic character. The decomposition reaction was found kinetically of zero order with energy of activation 10.5, 9.8 Kcal mol-1 for dysprosium butyrate and valerate, respectively. The X-ray diffraction measurement were used to calculate the long spacing and the result confirm the double layer structure of dysprosium soaps.